Characterization of chicken Relaxin3 gene: mRNA expression and response to reproductive hormone treatment in ovarian granulosa cells, and single nucleotide polymorphisms associated with egg laying traits in hens - Chunfeng Zhang; Yi Sun; Li Kang; Yunliang Jiang (Animal Biotechnology, 2024)
As a protein structurally similar to insulin, relaxin3 (RLN3) plays a role in promoting arousal, suppressing depressive or anxious behaviors. Two studies revealed the increase of RLN3 expression during chicken follicle selection. In this study, by real-time quantitative PCR and luciferase assay, mRNA expression and single nucleotide polymorphisms (SNPs) of chicken RLN3 were investigated. The mRNA expression of chicken RLN3 was higher in the granulosa cell of hierarchal follicles (Post-GCs) than that of pre-hierarchal follicles (Pre-GCs). In Pre-GCs, the mRNA expression of chicken RLN3 was stimulated by FSH and progesterone; in Post-GCs, it was stimulated by higher concentration of estrogen and FSH, however, was inhibited by progesterone. Four SNPs including g.-655G > C, g-592G > A, g.-372T > A and g.-282G > C were identified in the critical promoter region from −1291 bp to −207 bp of chicken RLN3, among which g.-655G > C, and g-592G > A were associated with age at first laying and clutch size, respectively, in Zaozhuang Sunzhi chickens. At g.-655G > C and g-592G > A, allele C and allele A had higher transcriptional activity, respectively. These data suggest that RLN3 plays an important role in chicken follicle development and SNPs in its promoter region are potential DNA markers for improving egg production traits.